Expression of 300-kilodalton intermediate filament-associated protein distinguishes human glioma cells from normal astrocytes. - Yang, H Y (1993)
The availability of biochemical markers to distinguish glioma cells from normal astrocytes would have enormous diagnostic value. Such markers also may be of value in studying the basic biology of human astrocytomas. The vimentin-binding, 300-kDa intermediate filament (IF)-associated protein (IFAP-300kDa) has recently been shown to be developmentally expressed in radial glia of the central nervous system of the rat. It is not detected in the normal or reactive astrocytes of the adult rat nor in neonatal rat brain astrocytes in primary culture. In the present study, double-label immunofluorescence microscopy using antibodies to IFAP-300kDa and glial fibrillary acidic protein (GFAP, an astrocyte-specific IF structural protein) identifies this IFAP in GFAP-containing tumor cells from examples of all three major types of human astrocytomas (i.e., well-differentiated, anaplastic, and glioblastoma multiforme). Astrocytoma cells in primary cultures prepared from all three astrocytomas also express this protein. It is not detectable in normal adult brain tissue. Immunoblot analyses using the IFAP-300kDa antibody confirm the presence of a 300-kDa polypeptide in fresh astrocytoma preparations enriched for IF proteins. These results suggest the utility of IFAP-300kDa as a marker for identification of human glioma cells both in vitro and in situ.